PEMBERDAYAAN MASYARAKAT ISLAM BERBASIS EKONOMI KREATIF DALAM MENINGKATKAN KEMANDIRIAN EKONOMI DI DESA KALISALAK BANYUMAS - Kuswantoro Kuswantoro (Da'wa Faculty UIN Saizu Purwokerto, 2022)
This study aims to identify the supporting factors of the rural economy. The implementation of creative economic development in rural areas must be designed by involving various economic and supporting institutions, including: universities, credit institutions, entrepreneurs, and community business groups. Community business groups function as business entities in rural areas. This research is a qualitative research using the method of observation and interviews with members of the Sentosa Mandiri Business Group. From this research, it can be seen that the Sentosa independent business group creates job opportunities for rural communities and forms a rural creative economy so that it increases people's income and ultimately improves the welfare of rural communities. Keywords: Empowerment, Creative Economy, Independent Business Group